2016
DOI: 10.2147/oas.s81552
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung disease: current perspectives

Abstract: Hirschsprung disease is a complex congenital condition of the intestine, which is recognized as being of genetic origin and results from a disturbance of the normal development of the enteric nervous system. As a result, aganglionosis of the distal bowel occurs. It is the most common cause of a low intestinal obstruction in the neonate as well as older children. Occurring as an isolated condition in 70% of cases, it may be associated with other associated congenital abnormalities as well as a number of syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 46 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…Diagnosis is then confirmed by other tests (e.g., histology of rectal biopsies). 3 Previous studies have shown the transition zone and reversed recto-sigmoid index as the most common radiological signs in CE. 14,34,35 The sensitivity and specificity of CE in the diagnosis of HD have shown a wide range, between 60%-100%.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Diagnosis is then confirmed by other tests (e.g., histology of rectal biopsies). 3 Previous studies have shown the transition zone and reversed recto-sigmoid index as the most common radiological signs in CE. 14,34,35 The sensitivity and specificity of CE in the diagnosis of HD have shown a wide range, between 60%-100%.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas normal babies pass meconium within 24 hours, and even up to 48 hours, any baby who passes no or little meconium even after 24 hours should be investigated for HD. 3 Intestinal obstruction presents with bile-stained vomit, and abdominal distention is often present by day 2. In developing countries, presentation may be significantly late, and the main symptoms include abdominal distention, constipation, or diarrhea, with failure to thrive and developmental delay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations